PENGETAHUAN REMAJA PUTRI TENTANG PERIKSA PAYUDARA SENDIRI Di SMA ADVENT TOMPASO - Gabriella Tulungen; Monalisa Sitompul (Jurnal Kesehatan, 2022)
BSE is a method that is most effective and also easy to do for every woman, both teenagers and adults. However, despite the many benefits and easy methods, there are still many women out there, especially at the age of teenagers who don't know and want to do BSE. High school students are a period of development from children to adults. The purpose of this study was to determine the level of knowledge of young women about BSE examination. The method used is quantitative with a pre-experimental research design with a one-group pretest post-test design. Respondents in this study 100 people. The research instrument used a test in the form of multiple choice questions made by researchers related to the material presented. The results of the Wilcoxon test showed p < 0.05, which means that BSE education is effective in increasing the knowledge of high school students. Suggestions that BSE material can be given in the learning process at school.